PENGGUNAAN METODE SIMULASI UNTUK MENINGKATKAN HASIL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS IX.B SMP N 6 LUBUK BASUNG - Mardiati, Mardiati (STKIP PGRI Sumatera Barat, 2015)
The purpose of this research in general is to address learning problems in SMP Negeri 6 Lubuk Basung. Specifically, this study aims to improve student learning outcomes through the use of simulation methods in the Pendidikan Agama Islam (PAI) in the class IX.B SMP Negeri 6 Lubuk Basung. The results showed the use of simulation method succeeded in improving student learning outcomes. In the first cycle, in classical only 46.6% of the total students in the class IX.B SMP 6 Lubuk Basung that achieve mastery learning with class average value reached 6.96, while in the second cycle which increased 76.6% of the total number of students has reached the thoroughness with an average value of 7.8 class. Based on these results it can be concluded that the use of simulation methods succeeded in improving student learning outcomes Pendidikan Agama Islam (PAI) in the class IX.B SMP N 6 Lubuk Basung.